New data on the fungus gnats from the Russian Far East (Diptera: Sciaroidea). Contributions to the knowledge of East Palaearctic insects (4). - Zaitzev, Alexander I.; Menzel, Frank (Contributions to Entomology = Beiträge zur Entomologie, 1996)
The present publication summarizes records of eleven species of fungus gnats (Sciaroidea: Ditomyiidae, Keroplatidae, Mycetophilidae) which were collected in the Russian Far East (Primorskiy Kray) during the second expedition of the German Entomological Institute. The following seven species are new to science: Ditomyia klimovae sp. n., Orfelia subnigricornis sp. n., O. ussuriensis sp. n., Neoplatyura cornuta sp. n., Urytalpa attenuata sp. n., Neoempheria aperta sp. n., Trichonta subterminalis sp. n. Megophthalmidia takagii Sasakawa is recorded from Russia for the first time.Nomenclatural Actsklimovae Zaitzev & Menzel, 1996 (Ditomyia), spec. n.aperta Zaitzev & Menzel, 1996 (Neoempheria), spec. n.cornuta Zaitzev & Menzel, 1996 (Neoplatyura), spec. n.subnigricornis Zaitzev & Menzel, 1996 (Orfelia), spec. n.ussuriensis Zaitzev & Menzel, 1996 (Orfelia), spec. n.subterminalis Zaitzev & Menzel, 1996 (Trichonta), spec. n.attenuata Zaitzev & Menzel, 1996 (Urytalpa), spec. n.